THE ROLE OF MEDIUM OF INSTRUCTION IN FUNCTIONAL LITERACY IN KAZAKHSTAN: A COMPARATIVE, INFERENTIAL, AND VALUE-ADDED ANALYSIS - Tlessov, Alisher (Nazarbayev University Graduate School of Education, 2024)
The medium of instruction has been a controversial issue in Kazakhstan as the two main mediums (Kazakh and Russian) have had unequal status due to a unique historical context. During the Soviet era, Kazakh medium schools faced severe restrictions and funding cuts, while Russian medium schools were deliberately prioritized and provided effective functioning. Although Kazakh medium schools have been supported since independence, the perceptions of inferiority surrounding the Kazakh sector may persist. Such perceptions may arise not only from Soviet ideologies but also from the Programme for International Student Assessment (PISA), which found that the Russian sector outperformed the Kazakh sector in functional literacy across all cycles. However, PISA has a major limitation as it is a one-time assessment. To offer a broader picture, this quantitative research utilized unique data from the Centre for Pedagogical Measurements (CPM), which conducted large-scale assessments on the same population of students and schools in April 2021 and January 2022, testing their reading, scientific literacy, and mathematical literacy proficiencies across several oblasts of Kazakhstan. Employing advanced educational modeling techniques, this research made three interconnected studies. The first comparative Rasch modeling study found that Russian medium students had significantly higher ability estimates at two time points. The second multilevel modeling study revealed that Russian medium predicts achievement in reading and scientific literacy and growth in achievement in reading literacy. While these studies found the superior performance of the Russian sector, the third VAM study found that some Kazakh medium groups significantly and practically added the highest value to students’ mathematical and scientific literacy abilities, while Russian medium groups added the lowest value to scientific literacy abilities. The research findings imply that while Kazakh sector may broadly need help in materials and resources, the Ministry of Education should provide targeted, research-based support for both mediums of instruction.
Keywords: Type of access: Embargo; medium of instruction; MOI; functional literacy; school effectiveness; Rasch modeling; multilevel modeling; value-added modeling